# Identify each system as linear-quadratic or quadratic-quadratic. Then solve. 1. y=x-1 x^2+y^2=25 2. 9x^2+4y^2=36 x^2-y^2=4 3. -x+y=4 y=x^2-4x+2

*print*Print*list*Cite

Student Comments

pramodpandey | Student

Linear equation has form

ax+by=c

quadratic has form

`ax^2+bx+c=0`

linear quadratic equation

`ax+by^2+cy+d=0`

quadratic-quadratic as

`ax^2+by^2=c`

Thus

1. y=x-1 (linear )

x^2+y^2=25 ( quadratic-quadratic)

2. 9x^2+4y^2=36 (quadratic-quadratic)

x^2-y^2=4 (quadratic-quadratic)

3. -x+y=4 (linear )

y=x^2-4x+2 (linear quadratic)